Aplikasi Pencarian SMA/SMK DI Wilayah Jakarta Barat Berbasis Android - ramadhan, aditya (STMIK Palangkaraya, 2019)
Education is one of life's necessities which people should have. An individual will again wider perception and knowledge needed for his future with it. Technology development help people receive information in seconds via smartphone. Lately, smartphones are able to provide more services, such as Global Positioning System (GPS) which allows users to locate their position or search a certain place. It makes searching school location and information about the building easier. With this android-based application, parents and students can easily search information with location indicator. Location Based Service(LBS) is an information service in the shape of location indicator on a smartphone and can be accessed using mobile network Keyword : Android, Education, GPS, Location Based Service (LBS), Mobile